Islam Nusantara sebagai Paradigma Ustadz Hanan Attaki - Hasan, Ahmad (Panangkaran: Jurnal Penelitian Agama dan Masyarakat, 2025)
Particularly in Indonesia, Islam Nusantara is a view initiated by Nahdlatul Ulama (NU) in response to geographical dispersion. Traditionalist Islam, also known as Islam Nusantara, is a Sufi-inspired orientation and is often generalized in NU discourse as Indonesian Islam, thereby ignoring the differences between the two. It is a hybrid form of Islam developed mainly in Java since the 16th century, which gradually blended with Javanese adat (customary law), Hinduism, Buddhism, and mystical practices. Through this argument, the phenomenon of hijrah, especially in Indonesia, has become the author's concern, one of which is the latest, namely the inclusion of Ustad Hannan Attaki in the largest organization in Indonesia, even the world, namely Nahdlatul Ulama. This study aims to describe aspects of Nahdlatul Ulama-style Islam Nusantara that can influence Ustad Hannan Attaki's views. This research is a type of descriptive qualitative research with various literature reviews. The results of this article show that the authority of Kiai as the main component of Nusantara Islam has influenced Ustad Hanan Attaki's thinking paradigm, especially through the figure of KH. Marzuki Mustamar. For Ustaz Hanan Attaki, KH. Marzuki is not only a representation of scientific sanad, but also a role model. He realizes that adhering to Ahlusunnah wal Jamaah is not enough without NU attachment, so allegiance to Nahdlatul Ulama is a form of commitment to peaceful da'wah.